From Kyoto Protocol to Paris Agreement: An Analysis of Global Climate Regime Changes Based on a Study of the Evolution of Green Gases Emissions Profiles - Maria Cristina Oliveira Souza (Desenvolvimento e Meio Ambiente, 2017)
This paper uses the notion of climate regime provided by the International Relations literature and by interdisciplinary approaches on climate change. Such notion is important to understand the global normalization of the problem of climate change. Quantitative and qualitative data on greenhouse gas emissions, provided by Climate Sciences and the Economics of Climate Change, are used in order to present and discuss recent changes in emissions profiles of selected countries involved in the global climate governance. In line with these changes, the climate regime has also been transformed. The mentioned changes include the emergence of a "bottom-up" approach, represented by the Paris Agreement, which crowned the 21st Conference of the Parties to the UN Framework Convention on Climate Change at the end of 2015. It is regarded as an alternative to "top-down" approach that characterized the negotiations under the aegis of the Kyoto Protocol. The discussion is based on the analysis of changes in profiles of greenhouse gas emissions by the countries that were part of the original architecture of the Kyoto Protocol, as well as other groupings that took shape during the successive rounds of negotiations, especially BASIC, a group formed by Brazil, South Africa, India and China. Recent interest configurations have been shown to give rise to new coalitions and leadership in negotiations on the issue, while reinforcing old conflicts and creating new tensions. Thus, the discussion proposed in this article should provide elements for understanding the directions of international climate negotiations that have led to a reconfiguration of the architecture of the climate regime, with substantive changes in terms of leadership, coalition of countries and attribution of responsibilities.